Sensitivity and specificity of the enzyme-linked immunoelectrotransfer blot test (EITB) for the diagnosis of hydatidosis in sheep - Bardales-Ortiz, Karina (2022)
The aim of the study was to evaluate the enzyme-linked immunoelectrotransfer blot test (EITB) in the serological diagnosis of ovine hydatidosis. In total, 80 Corriedale sheep from SAIS Pachacútec, Junín, Peru, were used and the results compared with the necropsy (gold standard). The simultaneous presence of three antigenic bands (8, 16 and 21 kDa) in the EITB was considered a positive result, while the necropsy result was positive if there was at least one cyst in the liver or lungs. The EITB showed a low sensitivity (31.2%) and a high specificity (100%). Likewise, positive (PPV) and negative (NPV) predictive values of 100 and 5.4%, respectively, but without significant association (p=0.55) between the test result and the presence of cysts. To determine the usefulness of EITB in the detection of active cysts, the presence of at least one antigenic band was considered as positive and as an active cyst (active infection) the structure that, due to its macroscopic conditions, could contain cells capable of proliferating under adequate conditions. The results showed a high sensitivity (93.6%) of the test to identify active cystic lesions with PPV of 60.3% and NPV of 57.1%, although the results were not statistically significant (p=0.439). The findings show that the EITB test reaction is not necessarily more sensitive when active cysts are present.